The Correlation Between Job Stress And Work Motivation Of Special School Teachers In Pangandaran District - Setiawan (HealthCare Nursing Journal, 2025)
Work stress for Special School (SLB) teachers is caused by mental and physical fatigue in teachers because Children with Special Needs (ABK) require extra training and attention. The work stress experienced by special school teachers can be negative or positive on motivation depending on how the individual views the stressor. This research aims to determine whether there is a relationship between work stress and the work motivation of Special School teachers in Pangandaran Regency. This research method uses a quantitative and descriptive correlation research design using a cross sectional approach. The population in this study were special school teachers in Pangandaran Regency with a total of 53 teachers. The sampling technique in this research was a total sampling of 53 teachers. The questionnaire used in this research is the Indonesian version of the DASS-42 (Depression Anxiety Stress Scale) which uses a stress scale only to measure work stress variables and a work motivation questionnaire to measure work motivation variables. Data analysis in this research consists of two types, namely univariate and bivariate analysis using analysis in the form of the Spearman rank correlation test. The research results show that there is no significant relationship between work stress and the work motivation of Special School teachers in Pangandaran Regency.